Youth Voter Perception of Political Parties - Teguh Setyawan Santoso (International Journal on Social Science, Economics and Art, 2021)
This research tries to see how youth voter perception (public senior high school) that exist in Medan to political parties. Youth voter is one of the important elements in the election. The election in 2014 was the first election for those categorized as youth voter. Youth voter have a fairly large amount, making it great potential for those who want to reap the vote in the election. In this case, political parties as the main participants in elections is a part that directly in contact with youth voter. However, the dynamics of Indonesian politics where political party members caught many criminal cases raises the question, how youth voter perception of the political party? Did the dynamics influence their perception? The theory is used to explain the perception is theory of David Krech and Fred Luthans. The elaboration of youth voter given by the electoral commission as part of the general elections in Indonesia. An understanding of the political parties can be seen explanation by Joseph Lapalomba, Myron Weiner, Carl Friederich, Roger Soltau and Sigmund Neumann. While further explanation of political parties expressed by Gabriel Almond. By using questionnaires as the main techniques of data collection, the study relies on the analysis of the interviews were obtained. Youth voter have a great enthusiasm to face an election. With the amount of information available, also with so many media intermediaries such information. However as noted earlier, political parties do not play a main role, but the negative news that emerged as the consumption of youth voter. Youth voter great enthusiasm, although supported by a large potential just is not without obstacles. Enthusiasm is merely ceremonial. Lack of interest in other substantive activities result of poor understanding of the whole electoral process.